PENGEMBANGAN MEDIA PEMBELAJARAN UNTUK MATA PELAJARAN KEWIRAUSAHAAN DI SMK DENGAN MENGGUNAKAN APLIKASI MACROMEDIA FLASH - as'ad, as'ad; Fitrah, Yundi; Suratno, Suratno (Program Magister Teknologi Pendidikan Universitas Jambi, 2013)
Development of entrepreneurial learning media is simple, attractive, effective and efficient and whether the development of the media can improve student learning outcomes. This study aims to (1) Produce a simple media entrepreneurial learning, quality, attractive, effective and efficient form of a product (software) for vocational students of class X, (2) Examine the impact of the use of instructional media to see the difference in the value of the pre-test before using product (software) with a post-test after using the product (software). This study is a research and development by following the model of the development of Lee & Owen which consists of five phases: (1) the stage of analysis (analisys), (2) the stage of design (design), (3) the stage of development (development), (4 ) phase of implementation (implemantation), (5) the stage of evaluation (evaluation). Development focused on entrepreneurship subjects of class X SMK first semester. Before the products tested beforehand validated by experts of material and media expert. Furthermore, the product tested to students through the three stages of testing individual, small group testing, and field trials. Subject product trials are students of SMK Negeri 1 Sarolangun class X. subject of this research trial for individual testing consisted of three students, to test a small group of ten students, and for field trials consisted of 30 students. The data collected in this study is the data of expert materials, data from media experts, and student response data from the aspect of media appeal. Data collection instrument in the form of sheet material and a questionnaire to experts and media expert questionnaire sheet to subject individual testing, piloting small groups, and field trials. Analysis of data using qualitative descriptive analysis. The results showed: (1) the quality of instructional media development with Macromedia Flash applications vocational entrepreneurship subjects in terms of aspects of material including both criteria. (2) in terms of aspects of media including both criteria. (3) student responses about the appeal of media including very interesting criteria (4) an increase in the value of the average post-test of the pre-test of 23.20% of the 30 students on field trials, with 27 students (90%) have achieved mastery learning. Based on these results, it can be disimpulkn that products developed instructional media is fit for use as a source of learning for students. Keyword: Software CPB media entrepreneurial learning.